Varying cross-sectional volatility in the South African equity market and the implications for the management of fund managers - H. Raubenheimer (South African Journal of Business Management, 2011)
Modern portfolio theory is founded on an understanding of longitudinal volatility but it is the cross-sectional dispersion among investment returns that provide active portfolio managers with their competitive investment opportunities. The varying cross-sectional volatility in the South African equity market provides varying opportunity sets for active managers: the higher the cross-sectional volatility, the greater the opportunity for active risk taking, all other things being equal. This article argues that cross-sectional volatility must be considered hand-in-hand with risk limits and active risk targets when investment mandates are set and when mandated risk compliance is monitored.
Keywords: 650